Physiotherapists demonstrate weight stigma: a cross-sectional survey of Australian physiotherapists - Setchell, J.; Watson, B.; Jones, L.; Gard, M.; Briffa, Kathy (Australian Physiotherapy Association, 2014)
Question: Do physiotherapists demonstrate explicit and implicit weight stigma? Design: Cross-sectional survey with partial blinding of participants. Participants responded to the Anti-Fat Attitudes questionnaire and physiotherapy case studies with body mass index (BMI) manipulated (normal or overweight/obese). The Anti-Fat Attitudes questionnaire included 13 items scored on a Likert-type scale from 0 to 8. Any score greater than zero indicated explicit weight stigma. Implicit weight stigma was determined by comparing responses to case studies with people of different BMI categories (where responses were quantitative) and by thematic and count analysis for free-text responses. Participants: Australian physiotherapists (n = 265) recruited via industry networks. Results: The mean item score for the Anti-Fat Attitudes questionnaire was 3.2 (SD 1.1), which indicated explicit weight stigma. The Dislike (2.1, SD 1.2) subscale had a lower mean item score than the Fear (3.9, SD 1.8) and Willpower (4.9, SD 1.5) subscales. There was minimal indication from the case studies that people who are overweight receive different treatment from physiotherapists in clinical parameters such as length of treatment time (p = 0.73) or amount of hands-on treatment (p = 0.88). However, there were indications of implicit weight stigma in the way participants discussed weight in free-text responses about patient management. Conclusion: Physiotherapists demonstrate weight stigma. This finding is likely to affect the way they communicate with patients about their weight, which may negatively impact their patients. It is recommended that physiotherapists reflect on their own attitudes towards people who are overweight and whether weight stigma influences treatment focus.